Norman Mailer - Foster, Richard Jackson, 1928- (University of Minnesota pamphlets on American writers, 1968)
Norman Mailer - American Writers 73 was first published in 1968. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions.